A study of piglets born by spontaneous parturition under uncontrolled conditions: could this be a naturalistic model for the study of intrapartum asphyxia? - Trujillo-Ortega, M.E.; Mota-Rojas, D.; Olmos-Hermàndez, et al., A. (Acta Biomedica Atenei Parmensis, 2007)
In order to evaluate how spontaneously born piglets could be a suitable model for the study of intrapartum hypoxia, 230 newborn piglets were studied. Out them, 8.3% (n = 19) died intrapartum, 21.7% (n = 50) were born with moderate-to-severe intrapartum hypoxia, and 70% (n = 161) were born with mild or no evidence of intrapartum distress. Piglets born without any evidence of intrapartum asphyxia weighed approximately 240 g lower than those born with intrapartum hypoxia and intrapartum-dead piglets (P<0.0001). The viability score was approximately 3 units lower and the latency to contact the udder was two times longer in the piglets surviving intrapartum hypoxia than in controls (P <0.0001). In comparison with the control group, metabolic acidosis was most severe among intrapartum-dead piglets followed by piglets surviving intrapartum asphyxia (P =0.002). According to a multiple linear regression analysis, pCO2 and lactate blood levels, and birth weight were identified as explanatory variables of viability score (r: 0.78; P <0.001). Viability score, K+ and lactate blood levels, and birth weight were identified as explanatory variables of latency to contact the udder (r: 0.80; P <0.001). In conclusion, the spontaneously-born asphyxiated piglet could be considered as a naturalistic model for the study of intrapartum asphyxia. Histopathologic and more rigorous functional and behavioral evaluations are still required to further characterize the model.